(untitled) (Bioscience Journal, 2017)
The aim of the present study was to evaluate selected ophthalmic and physiologic parameters in rabbits submitted to retrobulbar blockade with lidocaine, morphine or ketamine. Eighteen adult rabbits, seven males and eleven females, New Zealand White breed, weighing 3.9 Â± 0.7 kg were randomly assigned to perform the retrobulbar block according to the groups: LID (2% lidocaine without a vasoconstrictor - 7 mg kg-1); MOR (1% morphine - 1 mg kg-1) or KET (10% Ketamine - 5 mg kg-1). Ophthalmic and physiologic parameters were assessed, including lacrimal production using Schirmer tear test (STT), corneal touch threshold (CTT), pupillary diameter, intraocular pressure (IOP), pulse rate (PR), respiratory rate (RR), oxyhemoglobin saturation (SpO2), rectal temperature (RT) and systolic, mean and diastolic blood pressures (SAP, MAP and DAP) and were evaluated every 10 minutes for 70 minutes. All drugs used in the present study promoted central positioning of the eyeball for up to one minute later the retrobulbar administration in all cases. There was a significant increase of STT values in MOR and LID, when compared to baseline, while the CTT values had a significant decrease in all groups. KET kept the IOP values unaltered at the time points and there was a significant decrease of pupillary diameter in MOR. There was no significant change in PR, RR and SpO2; however, LID presented significantly lower values of SAP. MOR had increased values for RT when compared to the other two groups. The established parameters may help in ophthalmic procedures using retrobulbar nerve blocks.